Temperature dependency of thermal conductivity of solid phases for fatty acids - Bayram, U.; Aksoz, S.; Marasli, N. (SPRINGER, 2014)
Thermal conductivity variations with temperature of solid phases for lauric acid (LA), myristic acid (MA), pivalic acid (PA), and stearic acid (SA) have been measured with radial heat-flow method. Temperature dependencies of the thermal conductivity for same organic materials have been obtained by linear regression analysis. From graphs of thermal conductivity versus temperature, the thermal conductivity of solid phase at their melting temperature and temperature coefficients of thermal conductivity for LA, MA, PA, and SA have been found to be 0.37, 0.39, 0.23, and 0.35 W K-1 m(-1) and 0.00935, 0.00446, 0.01095, and 0.00295 K-1, respectively. The ratios of thermal conductivity of liquid phase to thermal conductivity of solid phase for LA, MA, PA, and SA have also been measured to be 0.52, 0.48, 0.25, and 0.59, respectively, with a Bridgman-type directional solidification apparatus.
Keywords: Thermal conductivity; Temperature coefficients of thermal conductivity; Radial heat flow; Fatty acids; ENERGY-STORAGE MATERIALS; LIQUID SURFACE ENERGIES; STEARIC-ACID; HEAT; SYSTEM; DSC; NEOPENTYLGLYCOL; Thermodynamics; Chemistry